The effect of a combination of propolis extract and bovine bone graft on the quantity of fibroblasts, osteoblasts and osteoclasts in tooth extraction sockets - Louisa Christy Lunardhi; Utari Kresnoadi; Bambang Agustono (Dental Journal (Majalah Kedokteran Gigi), 2019)
Background: Tooth extraction is a procedure frequently performed in the field of dentistry that can cause alveolar bone resorption during the healing process. Therefore, preservation of sockets is necessary to maintain alveolar bone which represents one of the important factors in the successful manufacture of dentures. A combination of propolis extract and bovine bone graft (BBG) can accelerate bone regeneration. Purpose: The purpose of this study was to determine the effects of a combination of propolis extract and BBG on the quantity of fibroblasts, osteoblasts, and osteoclasts in the tooth extraction socket. Methods: 56 Cavia cobaya were divided into eight groups. The lower left incisor of each subject was extracted and induced with polyethylene glycol (PEG), propolis extract + PEG, BBG + PEG, combination of propolis extract + BBG + PEG at a concentration of 2% active substance. Experimental subjects were sacrificed on days 3 and 7. Histopathological examination with a microscope at 400x magnification was conducted to calculate the quantity of fibroblasts, osteoblasts, and osteoclasts. Statistical analysis was performed by one-way ANOVA and Tukey HSD tests. Results: The highest average quantity of fibroblasts and osteoblasts and the lowest average quantity of osteoclasts occurred in the group to which a combination of propolis extract and BBG had been administered on both days 3 and 7. According to the statistical analysis results, all the treatment groups recorded a significant difference in the quantity of fibroblasts, osteoblasts, and osteoclasts with a p value: 0.000 (p<0.05). Conclusion: A combination of propolis extract and BBG can increase the quantity of fibroblast and osteoblast cells, while reducing the number of osteoclast cells in tooth extraction sockets treated with 2% concentration of the active substance.